(untitled) (World Economics and Finance Bulletin, 2026)
Tax control is an important component of financial control. It is implemented in the process of collecting mandatory payments from the production sector of the economy during the formation of centralized state funds. Therefore, tax control is essential for ensuring that taxpayers fulfill their obligations in accordance with legal requirements. Tax control has its own specific features in terms of its nature and implementation, and it involves complex legal relationships. Consequently, the scientific study of this process is a pressing issue. This article analyzes the role and significance of tax control as a form of financial control.